Development of Web-Based Media for Sports Physical Tests - Nanda, Fitri Agung; Hartati; Kurdi, Fauziah Nuraini; Syamsuramel (Universitas Negeri Semarang, 2024)
This research aims to produce a practical, valid and effective measuring tool for the physical training of FKIP Unsri physical education students. The method used in this research is the research and development (R&D) research method which produces products in the form of applications for measuring physical tests for various sports. The sampling technique used in the research was 3rd semester physical education students, FKIP Unsri. The data collection techniques used are validation tests, practicality tests and effectiveness tests. The instruments in this research are validation sheets, questionnaires and application use among students. Data analysis techniques are validity analysis, practicality and effectiveness analysis. Based on the research results, the physical test measuring instruments for various sports in this study were very valid with a percentage of 83.92% and the average of the two test results was 81.25%, so it was stated that the physical test measuring instruments for various sports that were developed were in the very good category. proper to use. The findings of this research are a software in the form of a practical and valid application that can be used to measure physical tests in various sports. The implication of the results of this research is that the application of measuring instruments for various sports can help coaches, athletes, students and students to be able to measure the process and results of training validly and easily because previously it was only done manually so measurement errors often occurred during training and training result.